2008
DOI: 10.1128/cmr.00013-08
|View full text |Cite
|
Sign up to set email alerts
|

Candida parapsilosis, an Emerging Fungal Pathogen

Abstract: SUMMARY Candida parapsilosis is an emerging major human pathogen that has dramatically increased in significance and prevalence over the past 2 decades, such that C. parapsilosis is now one of the leading causes of invasive candidal disease. Individuals at the highest risk for severe infection include neonates and patients in intensive care units. C. parapsilosis infections are especially associated with hyperalimentation solutions, prosthetic devices, and indwelling catheters, as well as the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

24
638
2
65

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 752 publications
(762 citation statements)
references
References 297 publications
24
638
2
65
Order By: Relevance
“…In fact, C. glabrata strains have frequently been isolated from patients with candiduria (Harris et al, 1999;Manzano-Gayosso et al, 2008) and are recognized as potentially pathogenic in hospitalized and catheterized patients (Fidel et al, 1999). As previously reported (Trofa et al, 2008), C. parapsilosis is not a frequent aetiological agent of UTIs. This was also evident in a recent epidemiological study of 100 candiduria cases (between 1999 and 2004) in a paediatric hospital in Brazil.…”
Section: Discussionsupporting
confidence: 69%
“…In fact, C. glabrata strains have frequently been isolated from patients with candiduria (Harris et al, 1999;Manzano-Gayosso et al, 2008) and are recognized as potentially pathogenic in hospitalized and catheterized patients (Fidel et al, 1999). As previously reported (Trofa et al, 2008), C. parapsilosis is not a frequent aetiological agent of UTIs. This was also evident in a recent epidemiological study of 100 candiduria cases (between 1999 and 2004) in a paediatric hospital in Brazil.…”
Section: Discussionsupporting
confidence: 69%
“…After C. albicans , it is the second or third leading cause of invasive candidiasis [14]. In particular, low birth weight infants are at increased risk for C. parapsilosis infection [15,16]. Previously, we demonstrated that C. parapsilosis is also able to produce immunomodulatory prostaglandins from exogenous arachidonic acid.…”
Section: Introductionmentioning
confidence: 99%
“…Candida parapsilosis is a well-known cause of nosocomial bloodstream infections, particularly among neonates and immunocompromised patients, and it is associated with candidaemia caused by intravascular and parenteral nutrition devices (Sarvikivi et al, 2005;Almirante et al, 2006;Pfaller & Diekema, 2002;Trofa et al, 2008). C. parapsilosis groups I, II and III were recently established as distinct species, which were classified by genotyping and designated C. parapsilosis sensu stricto, C. orthopsilosis and C. metapsilosis, respectively (Tavanti et al, 2005).…”
Section: Introductionmentioning
confidence: 99%